2001
DOI: 10.1080/080394801681019084
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of delayed social maturation and mental health disorders in young adults chronically ill since childhood

Abstract: To ascertain the influence of juvenile-onset chronic physical diseases and associating factors of social environment on delayed social maturation and mental health disorders in young adults, we analysed a group of 407 (184 female, 223 male) subjects with these conditions and compared the results with those of 123 (63 female, 60 male) healthy controls studied at the age of 19-25 years. The social maturation index was formed on the basis of a demographic interview, which also reviewed the state of social develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…They may feel restricted in social situations as a result of physical or emotional consequences of their conditions. This is undesirable, especially in adolescence, because close peer relationships are an important source of support for chronically ill or disabled adolescents at a time when they have to face developmental tasks and disease-related challenges [24,25]. Research showed that the majority of the young people with a paediatric condition have peer relations and friendships that are similar to those of their peers [26].…”
Section: Discussionmentioning
confidence: 99%
“…They may feel restricted in social situations as a result of physical or emotional consequences of their conditions. This is undesirable, especially in adolescence, because close peer relationships are an important source of support for chronically ill or disabled adolescents at a time when they have to face developmental tasks and disease-related challenges [24,25]. Research showed that the majority of the young people with a paediatric condition have peer relations and friendships that are similar to those of their peers [26].…”
Section: Discussionmentioning
confidence: 99%
“…Routine HRQOL assessment can facilitate detection and discussion of psychosocial issues related to chronic health conditions. Moreover, it can provide a chance to refer patients with significant risks of an unfavorable psychosocial outcome for interventions and to help these patients to achieve optimal development [20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Younger people are usually more sensitive to prejudice attitudes from their peers and other people with less well-adaptive coping strategies (Chittleborough et al, 2011; Geist, Grdisa, & Otley, 2003; Kokkonen, Kokkonen, & Moilanen, 2001). In addition to dealing with their infection, young PLWHA may also need to cope with stressors from physical changes, financial balance, and self-identity (Chittleborough et al, 2011; Geist et al, 2003; Kokkonen et al, 2001). Middle-aged people might bear the responsibility of taking care of their families/parents, and endure job-related pressures, which is particularly evident in Chinese settings.…”
Section: Conceptual Frameworkmentioning
confidence: 99%